The Christian structure of politics : on the De regno of Thomas Aquinas - McCormick, William A., S.J (Book collections on Project MUSE., 2022)
"This book focuses on the question, what is the relationship between Christianity and politics? The author argues that the De Regno of Thomas Aquinas offers an answer; discusses Aquinas's themes in the history of Christian political thought"--